Effectiveness of Shade Levels on The Performance of Pseuderanthemum Graciliflorum and Melastoma Malabathricum for Urban Landscape Use - Sayuti, Zulhazmi (2005)
A study of different shade levels on two selected native flowering shrubs namely Pseuderanthernum graciliflomm and Melastoma malabathricum was carried out at the Horticulture Research Centre, MARDI, Serdang, Selangor from February 2003 until May 2004. Both plants were propagated and established within one month before transferred under shading treatment. The plants were put under 4 levels of shade treatments i.e. 0%, 25%, 50% and 80%. The plots were arranged in Split-plot design with four replications. The main plots were 4 different shade levels while the subplots were both species. The parameters measured were the leaf area, total leaf area, chlorophyll content (SPAD), specific leaf area, leaf area ratio, leaf weight ratio, relative growth rate, root-shoot ratio, AICi curve, light response curve, Amax, Jmax, apparent quantum yield, RuBP capacity, nett photosynthesis, flower production and also consumer preferences. The results from this study showed that the growth performance of Pseuderanthemum graciliflorum under 25% shade and Melastoma malabathricum under 0% shade had the best growth in terms of their chlorophyll contents and specific leaf areas. Shading was also found to influence the gas exchange of both species in this study. The results showed that Jmax values were not significantly different on shoot for both species but have significant difference on mature leaf. Jmax values were highest on mature leaf of P. gracilinorum and Ad. malabathricum when grown under full sunlight. However, the plants decreased the rate of potential electron when exposed to shading condition. The two species tested had the lowest mean for Jmax under 80% shade. There were no significant difference in RuBP capacity at all levels of shading. However there were significant differences in Amax on mature leaf and apparent quantum yield on shoot and mature leaf for all shading treatments. Plant characterization through flower production indicated that P. graciliflorum was flowering at all shade levels compared to M. malabathricum which only flowered under 0% and 25% shade. M. malabathricum had a decreased number of flowers of more than 50% when shading was increased and had a one week delay to first flowering. A survey of consumer preferences that were carried out using 30 respondents consisting of landscape contractors and horticulturists indicated that they preferred P, grauliffomm grown under 25% and 50% shade. On the other hand M. malabathricum grown under 25% shade was preferred. Pseuderanthemum gracilifforum was also chosen to be suitable as potted plants and grown as hedges. Meanwhile, M. malabathricum was preferred only as a potted plant for outdoor landscape planting. The results also indicated that P. gmciliflomm was a shade loving plant while M. malabathricum was a sun loving plant. These results can determine the suitability and functional properties of both species for planting in urban areas